Checking up to keep on track: An Aboriginal-led approach to monitoring well-being. (September 2021) - Kelly, Linda; Whiteside, Mary; Barich, Hayley; Tsey, Komla
This article reports the process of identifying a well-being monitoring and evaluation approach for a community development programme with Aboriginal Native Title Holders in Northern Australia. The process involved the use of an empowerment-based Aboriginal Family Well-Being framework to enable Native Title Holders to articulate domains of value to their local community. These domains aligned with an existing culturally sensitive Aboriginal well-being survey tool which the Native Title Holders saw as relevant for their use. The attempts to provide Aboriginal people with a broader and more long-term perspective from which to judge the value of short-term projects is a different approach to traditional programme assessment (monitoring and evaluation). It aims to provide Aboriginal people with a more relevant frame from which they can make judgements about the worth of any programme or project in their location, supporting local control and decision-making. Potentially it provides Aboriginal people with the information from which to advocate for other supports and to assess the value of Government and other projects.